2013
DOI: 10.1093/ejcts/ezt089
|View full text |Cite
|
Sign up to set email alerts
|

Surgical technique for heart transplantation: a strategy for congenital heart disease

Abstract: The standard techniques for orthotopic heart transplantation often require certain adjustments when the procedure is carried out for complex congenital heart disease. This is because of both the unusual anatomy and possible distortions caused by previous surgery. Such technical adjustments have been described in various published reports over the years. Those reports, when combined, do cover the full spectrum of the technical difficulties that may be encountered, whether the defects are in their original form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…1 In the early 1960s, the classic technique for heart transplantation was developed, but another technique (bicaval anastomosis) was developed at nearly the same time. 2 Currently, bicaval anastomosis is frequently used because of its hemodynamic benefits due to the fact that sinus node function seems to be better preserved. 3 However, it can have some complications such as vena caval anastomotic stenosis or strictures, which may lead to superior vena cava (SVC) syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the early 1960s, the classic technique for heart transplantation was developed, but another technique (bicaval anastomosis) was developed at nearly the same time. 2 Currently, bicaval anastomosis is frequently used because of its hemodynamic benefits due to the fact that sinus node function seems to be better preserved. 3 However, it can have some complications such as vena caval anastomotic stenosis or strictures, which may lead to superior vena cava (SVC) syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…3 More classically, an anastomosis may be made within the RA rather than at the vena cavae, whilst other adjustments may need to be made to account for distortions present as a result of previous cardiac surgery or congenital abnormalities. 4 It can therefore be a challenge to interpret the initial information being gained during mapping if the full details of the surgical technique previously used are not known.…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have reported several surgical techniques for reconstructions of PLSVCs in patients undergoing OHT (Table 2) (Fig. 4) [3][4][5][6][7][8][9][10][11][12][13]. The interposition technique uses a synthetic graft to repair the PLSVC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, donor's en-bloc innominate veins can be used for a reconstruction of the PLSVC to avoid the use of a synthetic graft (Fig. 4c) [5,6]. Using donor's innominate veins is a simple technique because the technique does not require dissection of PLSVC from the atrioventricular groove.…”
Section: Discussionmentioning
confidence: 99%